2020
DOI: 10.1101/2020.05.04.20090399
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of the Potential Impact of COVID-19 Responses on the HIV Epidemic: Analysis using the Goals Model

Abstract: We applied a simulation model of HIV to analyze the effects of 3 and 6-month disruptions in health services as a result of COVID-19. We found that disruptions to primary prevention programs (male circumcision, behavior change programs, condom distribution) would have small but transitory effects on new infections that might be more than offset by reductions in commercial and multi-partner sex due to lock downs. However, if COVID-19 leads to disruptions in ART services the impacts on mortality could be severe, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 4 publications
0
13
1
Order By: Relevance
“…Biomarker data from the South African National HIV program show a 10‐fold increase in ALHIV aged 15–19 years receiving ART between 2005–2008 and 2015–2016, with an estimated 66% of all diagnosed ALHIV receiving ART by 2016 [ 8 ]. Recent modelling, however, shows that these gains will be halted by COVID‐19‐affected healthcare changes and ensuing lockdowns [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Biomarker data from the South African National HIV program show a 10‐fold increase in ALHIV aged 15–19 years receiving ART between 2005–2008 and 2015–2016, with an estimated 66% of all diagnosed ALHIV receiving ART by 2016 [ 8 ]. Recent modelling, however, shows that these gains will be halted by COVID‐19‐affected healthcare changes and ensuing lockdowns [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent events related to police brutality and violence against people of color and the COVID-19 pandemic represent additional stressors that will likely exacerbate the SAVAME syndemic among Latinos and other racial and ethnic minorities in the United States (Koran, 2020;Lopez et al, 2020). Some evidence suggests that COVID-19 is resulting in reduced access to HIV treatment (Stover et al, 2020), increases in DV (Taub, 2020), and exacerbation of mental health and substance use problems (Monteiro et al, 2020;Panchal et al, 2020). Conversely, disparities in SAVAME factors are likely to increase susceptibility and vulnerability to COVID-19 among Latinos (Substance Abuse and Mental Health Services Administration, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…18 52 People with HIV Nineteen studies assessed PLHIV. [54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72] Three modelling studies predicted a significant increase in HIV-related deaths in African countries due to treatment disruption with the pandemic. [61][62][63] A US retrospective observational quantitative study found that shelter-inplace orders had a negative impact on antiretroviral therapy adherence, especially among homeless PLHIV.…”
Section: General Publicmentioning
confidence: 99%